Parathyroid scintigraphy protocols in Finland in 2010 - Tunninen, V.; Kauppinen, T.; Eskola, H.; Koskinen, M.O. (Nuklearmedizin - NuclearMedicine, 2010)
The goal of this study was to describe current clinical parathyroid scintigraphy (PS) protocols in Finland. Methods: All departments of nuclear medicine in Finland were contacted, and instructions regarding PS were requested. Results: Instructions regarding PS were received from all of the departments that perform PS (n = 19). Seven hundred and sixtynine PS studies were performed in 2009 (between 7 and 209 per hospital). Three methods of PS were used. The dual-phase method with 99mTc-sestamibi is used in seven hospitals, the dual-tracer method with 123I/99mTc-sestamibi in eleven, and 99mTcO4/99mTc-sestamibi in one hospital. The activities of 99mTc-sestamibi, 123I and 99mTcO4 were 150–800 MBq, 10–30 MBq and 50 MBq, respectively. The anterior image with parallel-hole collimators, the anterior image with pinhole collimator, the oblique angles with pinhole collimator, SPECT and hybrid CT with SPECT were acquired in 84%, 26%, 16%, 63%, and 42% of the hospitals, respectively. Because the imaging techniques were combined, one to four acquisitions were performed per patient. Scatter and attenuation correction were used in five protocols. A correction for crosstalk of 123I and 99mTc gamma energies was not used, but the amount of crosstalk was decreased by using narrow or asymmetric energy windows in all dual isotope protocols. Conclusion: 19 hospitals used 18 different study protocols. Thus, significant variability exists in the current practice of PS in Finland. The protocols should be tested with known phantoms to determine any differences in sensitivities for detecting small active structures. Further studies with phantoms are needed to determine the optimal imaging techniques. The results of these phantom studies will provide guidelines for proposing national recommendations for PS.
Keywords: Hyperparathyroidism; parathyroid scintigraphy; 99mTc-sestamibi; iodine-123; numerical data